Pollen content accumulated in nests of Polybia scutellaris (Hymenoptera, Vespidae) - Fernandez Corujo, Victoria Lilian (2010)
Plant resources foraged by Polybia scutellaris were identified by analysing the pollen content of 14 nests in Magdalena (Buenos Aires Province, Argentina). Six nests were inhabited at the time of collection. The palynological analysis indicated that the wasps visited 33 different taxa of flowering plants during the active cycle of the colonies. Flowers visited by the wasps belonged to both native and exotic plants located close to the nests. The variety of resources foraged by P. scutellaris characterises this species as a generalist flower visitor.